Video Projection Mapping as a Visual Urban Art Performance on Architectural Facade - Işıkkaya, Ali Devrim (Street Art & Urban Creativity, 2023)
Video projection mapping as a contemporary visual public art today is the representative of interactive communication and media-architectural complexity in which the gathering of fiction and reality is observable. Video projection mapping (urban screenings), which transforms the facade into an interactive interface between the interior and exterior, provides also the conditions of a shared, creative, perceptual public atmosphere by triggering the reconstruction of the relations between art, games and the public spaces. This article inspects firstly about how public space / architectural facade relation is dialectically reconstructed and experienced throughout the video projection mapping implementations on architectural facades as a kind of conceptual collaboration – composition of physical public space, and virtual - perceptual space assembled in their specific epochs and contextually discusses their influences on urban society. This paper interprets the video projection mapping performances and tries to define the impact of this new public art, which is framed with space and time, on the city-dwellers. This article also aims to make a discussion on virtual urban reality, in terms of performative – virtual ‘surface’ architecture, or media-architecture. In conclusion, the future of video projection mapping as a visual art and architectural implementation in terms of public space - facade relation is speculated within the traces of current works and trends in the conclusion of the article.